Analisis Manajemen Kurikulum Di Perguruan Tinggi (Studi Kasus Pada Prodi MPI STAIN Mandailing Natal) - Siregar, Irma Suryani; Wahyuni, Sri (UIR Press, 2022)
Islamic universities as educational institutions must be able to produce superior, religious, intelligent, innovative and competitive human beings. One important aspect that must be considered is the suitability of the curriculum with the goals and vision of the university, especially for new study programs such as the Islamic Education Management Study Program at STAIN Mandailing Natal. The purpose of this study was to describe and analyze the planning, implementation, and evaluation of the curriculum of the MPI STAIN Mandailing Natal study program. This study uses a qualitative approach with data collection techniques documentation, interviews and observations of lecturers, students, education staff, leaders and so on. The data analysis technique was carried out in three stages, namely: data reduction, data presentation and conclusion drawing. The results of the study indicate that 1) Planning the curriculum of the MPI STAIN Mandailing Natal Study Program is carried out by: a) Formulating the vision and mission of the study program that refers to the vision and mission of STAIN Mandailing Natal; b) Determination of graduate profiles in accordance with the needs of stakeholders; c) Develop a curriculum structure; d) Prepare Syllabus and Semester Lesson Plans; 2) The implementation of the MPI STAIN Mandailing Natal Study Program curriculum is carried out in two systems, namely offline and online, using the Zoom meeting application, Google Meet and WhatsApp as a supporter; 3) Evaluation of the curriculum of the MPI STAIN Mandailing Natal Study Program, carried out by: a) context evaluation; b) Evaluation of inputs, related to curriculum documents, availability of lecturers, student readiness and adequacy of facilities and infrastructure; c) Process evaluation and result evaluation.